Discovery of toxin-encoding genes from the false viper Macropisthodon rudis, a rear-fanged snake, by transcriptome analysis of venom gland. (November 2015) - Zhang, Zhixiao; Zhang, Xi; Hu, Tingsong; Zhou, Weiguo; Cui, Qinghua; Tian, Jing; Zheng, Ying; Fan, Quanshui
Abstract: Although rear-fanged snakes are often considered as non-threatening to humans, some species are lethal or medically hazardous. The toxin components and bioactivities of front-fanged snakes have been extensively studied; however, only limited research has explored the venoms of rear-fanged snakes. The false viper, Macropisthodon rudis, is widespread in southern China, but little is known about the toxins that this snake produces. Here, we analyzed the transcriptome of the venom gland of M. rudis using high-throughput sequencing with an illumina HiSeq 2000. The raw data were assembled and annotated using public databases. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and gene ontology (GO) were analyzed. Using sequence comparisons, snake venom metalloproteinases (SVMPs) and a phosphodiesterase (PDE) were discovered in the venom gland of M. rudis . Highlights: This is the first transcriptomic study of the venom glands of Macropisthodon rudis . SVMPs and a PDE in the venom gland of M. rudis were first discovered in this study. The sequences of SVMPs and a PDE of M. rudis were homologous to front-fanged snakes.